PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA RENTAL MOBIL AKIBAT PENYEWA YANG BERIKTIKAD TIDAK BAIK - Elmanzah, Fajar; Sugiarti, Yayuk; Fithry, Abshoril (Jurnal Jendela Hukum, 2023)
The reason behind this research is the delay in returning the rental car that is not in accordance with the agreed time limit in the practice of car leasing. This research examines the problem of how legal protection for owner of car rental business and legal consequences for each party in the event of default on a car rental agreement based on Indonesian Civil Code. The research method used by the author to complete the thesis is the normative juridical legal research method, namely analyzing a problem based on laws and regulations and conducting literature studies such as book literature and other documents. The result of this research is to know that civil law protects the rights of entrepreneur who are harmed by renter based on the strength of the lease agreement in article 1320 and article 1338 of the Civil Code. Renters are also protected by law regarding their right to be free from liability due to force majeure based on articles 1244 and 1245 of Indonesian Civil Code. It can be concluded that business actors and renter must understand their respective responsibilities and rights and obligations based on existing legal rules based on the principle of good faith.